Effect of arginine-phosphate addition on early survival and growth of Scots pine, Norway spruce and silver birch - Häggström, Bodil (Swedish University of Agricultural Sciences, 2022)
The purpose of the research study was to investigate the effects of arginine-phosphate addition on survival and growth of Scots pine, Norway spruce and silver birch seedlings at three case studies in Sweden. The sites were located in the south (S), northeast (NE) and northwest (NW) parts of Sweden.

At the studies sites, forest had been harvested and mechanical soil preparation had been performed the same year as planting. Seedlings of Scots pine, Norway spruce and silver birch were planted in June 2019 at the NW site and June 2020 at the NE and S sites. At each site seedlings of the different species were planted in both in one-species and mixed plots, one plot treated with arginine-phosphate and on with untreated seedlings for each species composition. Survival- and growth inventory of was performed in august-september 2020 at the NW site and in 2021 at the NE and S sites, following two growing seasons in field.

The data consists of survival, height and stem base diameter measurements from the inventories.
The variables are described in detail in the documentation file.

Three data files are included, one for each site which were all analyzed separately:

a. effects_APtreatment_data_S_second_season.csv (1132 rows × 11 columns)
b. effects_APtreatment_data_NE_second_season.csv (1987 rows × 10 columns)
c. effects_APtreatment_data_NW_second_season.csv (1093 rows × 9 columns)

Also, the commented R script Code_manuscript_SND.R is included for reproduction purposes. It should be unpacked in the same directory as the data files. The PDF files in output_plots.zip are the plots generated from the script, and Code_manuscript_SND.log.txt contains log generated by the shell command:

Rscript Code_manuscript_SND.R > Code_manuscript_SND.log.txt

Syftet med den vetenskapliga studien var att undersöka effekterna av agininfosfat på överlevnad och tillväxt av tall-, gran- och vårtbjörksplantor på tre fallstudier i Sverige. De tre studerade lokalerna finns i södra (S), nordöstra (NÖ) och nordvästra (NV) delarna av Sverige.

Skogen på de studerade lokalerna var skördad och markberedning utförts samma år som plantering. Plantor av tall, gran och vårtbjörk planterades i juni 2019 på den nordöstra lokalen och i juni 2020 på de andra lokalerna. På varje lokal var de olika trädslagen planterade både var för sig och blandade ytor, med en yta behandlade med argininfosfat och en yta obehandlade plantor för varje trädslagskombination. Inventering av överlevnad och tillväxt utfördes i augusti-september 2020 på den nordöstra lokalen och 2021 på de andra lokalerna, följande två tillväxtsäsonger i fält.

Data består av överlevnad, höjd- och stambasdiametermätningar från inventeringarna.

Variablerna är beskrivna i detalj i dokumentationsfilen.

Tre datafiler är inkluderade, en fil för varje lokal som alla var analyserade separat:

a. effects_APtreatment_data_S_second_season.csv (1132 rader × 11 kolumner)
b. effects_APtreatment_data_NE_second_season.csv (1987 rader × 10 kolumner)
c. effects_APtreatment_data_NW_second_season.csv (1093 rader × 9 kolumner)

Det kommenterade R-skriptet Code_manuscript_SND.R har också inkluderats för reproduktion. Det skall packas upp i samma katalog som datafilerna. PDF-filerna i output_plots.zip innehåller de diagram som genereras av skriptet, och filen Code_manuscript_SND.log.txt innehåller logg från skriptet när det körts med terminalkommandot:

Rscript Code_manuscript_SND.R > Code_manuscript_SND.log.txt
Effekt av argininfosfattillförsel på tidig överlevnad och tillväxt av tall, gran och vårtbjörk
Keywords: seedling survival rate; seedling growth rate; forest regeneration; skogsföryngring; arginine; arginin; pine; tall (art); European white birch; vårtbjörk; Norway spruce; gran (art); Ecology; Ekologi